OPTICAL WAVELENGTH CONVERTERS IN FIBER OPTICAL NETWORKS - UTRERAS TELLO, A. J.; LICENKO, G. L.; REYES CIFUENTES, V. H.; MENA VILLACIS, R. I.; JARAMILLO PINOS, E. S. (Оптико-електроннi iнформацiйно-енергетичнi технологiї, 2018)
Optical Networks often use a wavelength converter as part of a switching system to improve their networks. Wavelength conversion is defined as a process by which the wavelength of the transmitted signal is changed without altering the data carried by the signal. The device that performs this function is usually called a wavelength converter but it is also referred to as a wavelength (or frequency) changer, shifter or translator. It is termed an up-converter when the converted signal wavelength is longer than the original signal wavelength and it is called a down-converter if the converted signal wavelength is shorter than the original signal wavelength. A wavelength converter should be capable of receiving an incoming signal at any wavelength (i.e. a variable wavelength) at the input port and must produce the converted signal at a particular wavelength (i.e. a fixed wavelength) at the output port. Therefore the input/output (I/O) ports of the converter must possess the capability of a variable input–fixed output (VIFO) converter and the majority of the optical switching networks use this type of device